Solid-state pulsed microwave bridge for electron spin echo spectrometers of 8-mm wavelength range - Kalabukhova, E. N.; Oleinik, V. V.; Savchenko, D. V.; Sitnikov, A. A.; Tsvir, A. V.; Ishchenko, M. G. (Technology and design in electronic equipment, 2025)
The article presents a construction of a coherent pulsed microwave bridge with an output power up to 10 Wt with a time resolution of 10–8 seconds at a pulse repetition rate of 1 kHz designed for electron spin echo spectrometers. The bridge is built on a homodyne scheme based on IMPATT diodes, which are used for modulation and amplification of microwave power coming from the reference Gunn diode oscillator. The advantages of the bridge are optimal power and minimum pulse width, simple operation, low cost.